Repeatability and Reproducibility of SMTube Measurement in Dry Eye Disease Patients - Yiran Hao; Lei Tian; Kai Cao; Ying Jie (Journal of Ophthalmology)
Purpose. To evaluate the intraobserver repeatability and interobserver reproducibility of Strip Meniscometry Tube (SMTube) and determine the correlations among the SMTube measurements and other ocular examinations in dry eye disease (DED) patients. Methods. The study recruited 73 eyes of 49 DED patients. Every subject was subjected to the following five measurements sequentially: the Ocular Surface Disease Index (OSDI) questionnaire, Tear Meniscus Height (TMH) assessment, SMTube measurements, tear film breakup time (BUT) examination, and Schirmer I test (SIT). The repeatability and reproducibility of the measurements were assessed by the intraclass correlation coefficient (ICC) and the Bland–Altman analysis, and the correlations were evaluated by the Spearman rank-order correlation. Results. The repeatability and reproducibility of the SMTube measurements were good in DED patients. The ICCs between the repeatability and reproducibility of the SMTube measurements were 0.789 and 0.741, respectively, and the Bland–Altman 95% limits of the repeatability and the reproducibility were −1.726 to 1.658 and −0.967 to 1.474, respectively (all P<0.01). The SMTube measurements had correlations with TMH, BUT, and SIT. The Spearman rank correlation coefficients between SMTube and TMH; SMTube and Schirmer I test; and SMTube and BUT were 0.632, 0.617, and 0.653, respectively (all P<0.01). Conclusions. The measurements of the SMTube may provide a novel, swift, noninvasive, and convenient approach to screen and diagnose DED with acceptable repeatability and reproducibility and specific correlations with TMH, BUT, and SIT.